Measurement of the lateral distribution function of UHECR air showers with the Pierre Auger Observatory - Barnhill, David (2005)
We describe how the lateral distribution function (LDF) is measured using the large sample of events recorded with the surface detector (SD) array and with a small sample observed with the fluorescence detectors (FD). For hybrid events, in which SD and FD measurements of the same shower are available, the core position is much better constrained than for SD-onlyevents, thus providing an important cross-check on the LDF determined from SD measurements alone.